2012
DOI: 10.1016/j.jcma.2012.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Number of involved lymph nodes is important in the prediction of prognosis for primary duodenal adenocarcinoma

Abstract: Subdivision of metastatic lymph nodes into N1 and N2 improves predictive ability. The seventh edition American Joint Committee on Cancer staging system is applicable in the present study with regard to the prediction of the prognosis for primary duodenal adenocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 36 publications
1
20
0
2
Order By: Relevance
“…The most common complications after PD are delayed gastric emptying and pancreatic fistula. The pancreatic fistula rate in the present study was 9·3 per cent, which is comparable to that reported in the literature (0–20 per cent).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The most common complications after PD are delayed gastric emptying and pancreatic fistula. The pancreatic fistula rate in the present study was 9·3 per cent, which is comparable to that reported in the literature (0–20 per cent).…”
Section: Discussionsupporting
confidence: 84%
“…Morbidity and mortality rates associated with surgical treatment for resectable duodenal cancer are high. Reported morbidity rates are around 40 per cent, and mortality rates range between 0 and 8·5 per cent ( Table S3 , supporting information).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,8,10,11,20,[22][23][24][25][26][27] In the largest single institution series of 122 patients who underwent PD for DA, LN involvement was found to be the only significant variable associated with survival on multivariate analysis. The 5-year survival was 68 % for node-negative patients, but only 17 % for those with N2 disease (defined as the presence of four or more positive nodes).…”
Section: Discussionmentioning
confidence: 95%
“…Performing a curative surgery, lymph node metastasis, and tumor stage were common significant prognostic factors in these studies (6,11,12). Moreover, patients with more than three lymph nodes positive for metastasis had significantly reduced overall survival (13). The estimated 5-year survival rates reach 46.4% after curative surgery (12).…”
Section: Discussionmentioning
confidence: 82%